2011
DOI: 10.1097/ico.0b013e31821b721c
|View full text |Cite
|
Sign up to set email alerts
|

West Indian (Caribbean) Punctate Keratopathy: Clinical and In Vivo Confocal Microscopical Findings

Abstract: West Indian punctate keratopathy should be considered in the differential diagnosis of scattered spot-like opacities with a history of residence in the endemic West Indies. Inflammatory entities can be excluded by in vivo confocal microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 6 publications
1
30
1
Order By: Relevance
“…Some patients were followed for up to 18 months and the opacities remained unchanged [ 1 ]. As we already indicate it seems to be rather frequent in the Antilles [ 1 , 2 ], but other publications confirmed that the condition was not restricted to people of African-Caribbean descent, but also presented in Caucasians and Hindus who had lived in the Antilles [ 2 , 4 , 5 ], and in other human groups of Central and South America [ 3 , 6 , 7 ]. Curiously it seems to be inexistent in Caucasians, Africans or Asians who have not lived in the Antilles or Central/South America.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Some patients were followed for up to 18 months and the opacities remained unchanged [ 1 ]. As we already indicate it seems to be rather frequent in the Antilles [ 1 , 2 ], but other publications confirmed that the condition was not restricted to people of African-Caribbean descent, but also presented in Caucasians and Hindus who had lived in the Antilles [ 2 , 4 , 5 ], and in other human groups of Central and South America [ 3 , 6 , 7 ]. Curiously it seems to be inexistent in Caucasians, Africans or Asians who have not lived in the Antilles or Central/South America.…”
Section: Discussionmentioning
confidence: 60%
“…Although there have been no other prevalence reported studies, anecdotal information based on experience of ophthalmologists working in the Antilles, have revealed that Punctate Keratopathy of West Indians seems to be a common ocular finding on those peoples [ 1 , 2 ]. This condition has also been reported in two Caucasians [ 2 , 4 ], two Hindus[ 2 ], and one north American Afro-Caribbeandescent [ 5 ], all of them sharing that they had previously lived in the Antilles. However, as already indicated, Punctate Keratopathy of West Indians is not limited to individuals related to those islands, and has also been found in Afroamericans and native Americans from Ecuador (SouthAmerica), and as well among mestizoes (mixed European and Native American ancestry) from Guatemala (Central America).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Recently Tietze et al 4 performed in vivo confocal microscopy in one case and described multiple punctate opacities located above the Bowman layer. There were no findings of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although only one published series from Grenada (Lesser Antilles in the West Indies) studied prevalence of the condition (6.25% rate),2 from anecdotal information based on experience of ophthalmologists working in the Antilles, it seems to be rather common among inhabitants of those islands;1 2 it has been also described in two Caucasians,2 3 two Hindus2 and one North American Afro-Caribbean descent,4 all of whom had lived in the Antilles. Moreover, the condition has been found in Native Americans and Afro-Americans in Ecuador5 and in two mestizoes (mixed European and Native American ancestry) from Guatemala 5.…”
Section: Introductionmentioning
confidence: 99%